Fifth International Conference on the History of Occupational and Environmental Health. Rotterdam (The Netherlands), April 24-25, 2014. - Riva, Michele Augusto (La Medicina del Lavoro, 2014)
The Fifth International Conference on the History of Occupational and Environmental Health took place at the Erasmus University Medical Centre (Erasmus MC) in Rotterdam (The Netherlands) on April 24th and 25th, 2014. The Conference was organized by the Yellow Factory, the Erasmus University and the Arnold Leuftink Foundation, with the collaboration of the ICOH Scientific Committee on History of Prevention of Occupational and Environmental Diseases. With this event, the ICOH international conference on History has returned in Europe, after the success of the forth conference, held in San Francisco (USA) in June 2010 (1, 3). ....